2021
DOI: 10.1167/tvst.10.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Visual Field Inference From Optical Coherence Tomography Using Deep Learning Algorithms: A Comparison Between Devices

Abstract: To develop a deep learning model to estimate the visual field (VF) from spectral-domain optical coherence tomography (SD-OCT) and swept-source OCT (SS-OCT) and to compare the performance between them. Methods:Two deep learning models based on Inception-ResNet-v2 were trained to estimate 24-2 VF from SS-OCT and SD-OCT images. The estimation performance of the two models was evaluated by using the root mean square error between the actual and estimated VF. The performance was also compared among different glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…However, they employed an Inception-v3 CNN instead of an SVM to predict the 24-2 VF map, reporting a root mean squared error (RMSE) of 4.79 dB across the 24-2 map. A follow-up study by Shin and colleagues 42 investigated the advantage of thickness maps generated by swept-source OCT (SS-OCT) versus spectral domain OCT (SD-OCT). RMSE was significantly lower at 4.51 dB for SS-OCT when compared to 5.29 dB for SD-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, they employed an Inception-v3 CNN instead of an SVM to predict the 24-2 VF map, reporting a root mean squared error (RMSE) of 4.79 dB across the 24-2 map. A follow-up study by Shin and colleagues 42 investigated the advantage of thickness maps generated by swept-source OCT (SS-OCT) versus spectral domain OCT (SD-OCT). RMSE was significantly lower at 4.51 dB for SS-OCT when compared to 5.29 dB for SD-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…Although DL has been used for diagnosing glaucoma in several studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 27 , 28 , 29 , 30 , 31 ], only a few have applied DL to UWF fundus images [ 31 ]. To the best of our knowledge, our study is the first to apply DL to true-colour confocal scanning images for diagnosing glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to incorporate deep learning (DL) into various imaging methods for diagnosing ophthalmologic diseases [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. There are many reports on the application of DL methods to conventional fundus imaging; [ 16 , 26 ] recently, it was reported that when optical coherence tomography (OCT) and DL methods are combined, excellent glaucoma diagnostic results can be achieved [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies from the same group compared different architectures for the DL model and different OCT technologies (SD and swept-source [SS] OCT). 16,17 Among the architectures tested, Inception-ResNet-v2 was superior to Inception-v3 and Inception-v4. Although the prediction errors were significantly lower, they were probably not clinically relevant.…”
Section: Prediction Of 24-2 Visual Field Sensitivity Threshold Valuesmentioning
confidence: 99%